2014
DOI: 10.1007/s12650-014-0252-z
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of pre-set vortices in boundary layer flow over wavy surface in rectangular channel

Abstract: Smoke-wire flow visualization is used to study the development of pre-set counter-rotating streamwise vortices in boundary layer flow over a wavy surface in a rectangular channel. The formation of the vortices is indicated by the vortical structures on the cross-sectional plane normal to the wavy surface. To obtain uniform spanwise vortex wavelength which will result in uniform vortex size, two types of spanwise disturbances were used: a series of perturbation wires placed prior and normal to the leading edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…The smoke-wire apparatus consisted of a Nickel-Chromium wire diameter of 0.193 mm, a pressurized container holding paraffin oil mounted on the top of the test section and a manual traversing mechanism as described by Nadesan et al (2014) and Budiman et al (2014). In practice, the oil container was fixed on the traversing mechanism movable in two axes.…”
Section: Description Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smoke-wire apparatus consisted of a Nickel-Chromium wire diameter of 0.193 mm, a pressurized container holding paraffin oil mounted on the top of the test section and a manual traversing mechanism as described by Nadesan et al (2014) and Budiman et al (2014). In practice, the oil container was fixed on the traversing mechanism movable in two axes.…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…Installing perturbation wires just before the leading edge may lead to the appearance of these vortices over concave surfaces amplified by centrifugal instability (Peerhossaini and Bahri 1998;Mitsudharmadi et al 2004). However, the leading edge pattern method is a more practical way to generate streamwise counter-rotating vortices (Budiman et al 2014;Hasheminejad et al 2014). In the present work, a triangular pattern (refer to Sec.2) is used at the flat plate leading edge to examine its effect on the development of such vortices.…”
Section: Formation and Development Of Streamwise Counter-rotating Vormentioning
confidence: 99%
See 1 more Smart Citation
“…This method was similar to that used by Hasheminejad et al [11] and the initial channel normal gap H is 35 mm, which gives the non-dimensionalized parameter S = a/H = 0.107. The channel width is 160 mm, which is sufficient to avoid the near wall effect from the [20]. During the experiments, the measured data were low-pass filtered at 3 kHz and sampled at 6 kHz for duration of 21 seconds.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The thicker part of the boundary layer is called the "upwash" region where low momentum fluid is ejected from the surface, while the thinner part is called the "downwash" region where high momentum outer fluid move towards the wall [19]. An earlier visualization study on laminar boundary layer flow by Budiman et al [20] showed that the presence of a wavy surface could delay the breakdown of such pre-set vortices until at least the first peak of corrugation, compared with the case for a flat plate.…”
Section: Introductionmentioning
confidence: 99%